Improving Literal Comprehension Reading Ability through Think-Tac-Toe Learning Strategy in Students with Dyslexia - Nabilla, Ihsa; Marlina, Marlina (Edumaspul: Jurnal Pendidikan, 2022)
Dyslexia students generally experience problems related to reading comprehension skills, one of which is the ability to read literal comprehension. Based on the results of the assessment, one of the dyslexic students in an inclusive school has a low literacy reading ability. The purpose of this study was to examine the effectiveness of the think-tac-toe strategy in improving literacy reading comprehension of students with dyslexia. Subject selection is done with the ability of children with special needs and as a man who understands literal understanding. Using a single subject research design type A-B-A reversal design. Data were collected by observation and tests. Observations used to observe observations of students’ literal understanding during the learning process. The oral test is done by asking the child to mention the answer to the question and the action test is done by asking the child to read the text and the answers on the worksheet given. Data analysis used visual graph analysis which consisted of analysis under conditions and analysis between conditions. The results of the study showed an increase in literal comprehension reading skills after the think-tac-toe learning strategy was applied. It is recommended to teachers that the think-tac-toe learning strategy be used as a new strategy model that is used to help students improve reading comprehension skills.